CatchML - A Language for Modeling and Verification of Context-Aware Exception Handling Behaviour - de Lima, Rafael; S. Rocha, Lincoln; M. C. Andrade, Rossana; Lelli, Valeria (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS), 2019)
The context-aware exception handling (CAEH) is an error recovery technique employed to improve the ubiquitous software robustness. The design of CAEH is a difficult and error-prone task. The erroneous specification of such conditions represents a critical design fault that can lead the CAEH mechanism to behave erroneously or improperly at runtime. To deal with this problem, we propose a domain-specific language for modeling CAEH, called CatchML, using a high-level interface to make the design of CAEH models simpler and more intuitive. The CatchML language is integrated into a tool to allow designers to perform automatic model verifications by looking at the errors directly in the specification code. We conducted a case study on a sample system called UbiParking with nine volunteers. The results showed that the CatchML language is easy to model the context-aware exception handling and also allowed the participants to quickly locate the injected design faults.